Pre-weaning goat kid mortality in communal production systems: a multifactorial synthesis of causes, risk factors, and mitigation strategies - Segakoeng, Moeketsi; Mpofu, Takalani; Mtileni, Bohani; Hadebe, Khanyisile (Frontiers in Animal Science, 2026)
Pre-weaning mortality in goat kids presents a major threat to food security and the economic sustainability of rural households that are already resource-limited. The herd growth remains slow, resulting in low population numbers in local goat populations. Current literature discusses pre-weaner mortalities disjointedly in terms of the regions and observable symptoms, often without the in-depth analyses of biological processes and the environmental interactions causing these problems. This review unpacks the multifactorial nature of pre-weaning goat kid mortality, focusing on the underlying interactions between genetic, biological, environmental, management, and socioeconomic determinants. This review explores historic trends of kid mortality, farmer dynamics, and practices such as unstructured traditional breeding systems, indiscriminate cross-breeding, and the lack of performance and pedigree data in traditional farming systems. Genetic factors contributing to pre-weaning mortality include breed, birth weight (BW), litter size (LS), and milk yield (MY) of the doe. Common infectious factors include gastrointestinal and respiratory diseases, while non-infectious factors include malnutrition and tick-borne diseases, particularly heartwater. The review underscores the imperative to migrate beyond symptom-focused treatment toward addressing root causes through improved management and collaborative resource sharing. Intervention efforts such as community-based breeding programs must integrate the selection of animals that have superior pre-weaning performance and functional traits. An understanding of the underlying morbidity pathways and their environmental, management-related, or genetic origins can support the development of holistic and context-appropriate mitigation strategies to enhance kid survival and strengthen the long-term sustainability of goat farming systems.